Food science : - Mehas, Kay Yockey (McGraw - hill, 1997)
In Food Science: The Biochemistry of Food and Nutrition students learn to use the scientific method as they study the biological and chemical basis of food and nutrition. The text combines scientific principles with real-life applications of food preparation and nutrition. It is taught by the Family and Consumer Sciences teacher, a Science teacher, or by the two together.